2013
DOI: 10.1128/jb.00903-13
|View full text |Cite
|
Sign up to set email alerts
|

The D3 Bacteriophage α-Polymerase Inhibitor (Iap) Peptide Disrupts O-Antigen Biosynthesis through Mimicry of the Chain Length Regulator Wzz in Pseudomonas aeruginosa

Abstract: L ipopolysaccharide (LPS) is an integral structural component of the outer membrane of Gram-negative bacteria and is important for the survival of these bacteria in the environment or in a host. In Pseudomonas aeruginosa and many other opportunistic pathogens, LPS is a major virulence factor and is composed of a lipid A membrane anchor, a core oligosaccharide linker, and a distal polysaccharide termed O antigen (O-Ag) (1). P. aeruginosa simultaneously produces two forms of O-Ag, a homopolymeric common antigen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 60 publications
2
24
0
Order By: Relevance
“…Islam et al suggested that the chain length of the Oag is determined by the interaction of Wzz and Wzy (40). Recent work of Taylor et al also suggested the direct interaction of Wzz and Wzy in the Oag biosynthesis pathway (41). In this study, for the first time, we were able to provide insight into the association of Wzy Sf and Wzz Sf in Oag biosynthesis.…”
Section: Discussionsupporting
confidence: 58%
“…Islam et al suggested that the chain length of the Oag is determined by the interaction of Wzz and Wzy (40). Recent work of Taylor et al also suggested the direct interaction of Wzz and Wzy in the Oag biosynthesis pathway (41). In this study, for the first time, we were able to provide insight into the association of Wzy Sf and Wzz Sf in Oag biosynthesis.…”
Section: Discussionsupporting
confidence: 58%
“…LPS is composed of a lipid A membrane anchor, a core oligosaccharide linker and a distal polysaccharide termed O-antigen, in the form of A and B bands (Taylor et al, 2013). Both WT and mutant forms of wzy and mucA genes were simultaneously found in the presently described mutants, suggesting that the mutation can reverse at a high rate.…”
Section: Cross-resistance and Reversibility Of Mutantsmentioning
confidence: 99%
“…Recent work on the D3 bacteriophage of P. aeruginosa revealed that the serotype switching mechanism is critically dependent on a small hydrophobic 3-kDa protein (Iap), which mimics the N-terminal transmembrane domain of the Wzz proteins and uses it to compete with chain-length regulators for binding to the endogenous Wzy polymerase (Taylor et al, 2013). Recent work on the D3 bacteriophage of P. aeruginosa revealed that the serotype switching mechanism is critically dependent on a small hydrophobic 3-kDa protein (Iap), which mimics the N-terminal transmembrane domain of the Wzz proteins and uses it to compete with chain-length regulators for binding to the endogenous Wzy polymerase (Taylor et al, 2013).…”
Section: Proposed Models Of O-antigen Chainlength Regulation In the Wmentioning
confidence: 99%